2017
DOI: 10.1007/s13258-017-0639-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of IGF1R expression with ABCG2 and CD44 expressions in human osteosarcoma

Abstract: Osteosarcoma is the most common type of malignant bone tumors. Insulin Growth Factor 1 receptor (IGFR1) has been known as a prognostic factor for metastasis of osteosarcoma. ABC subfamily G member2 (ABCG2) is related to resistance to anti-cancer drug, and CD44 has a role in tumor growth and metastasis. The purpose of this study is to investigate the relationship among expression patterns of IGF1R, ABCG2, and CD44 in osteosarcoma. The expression levels of IGF1R, ABCG2, and CD44 proteins were determined in tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…IGF-1R is a transmembrane tyrosine kinase receptor of the insulin receptor family and contains two extracellular α subunits and two transmembrane β subunits (45). Numerous studies have reported that IGF-1R is frequently overexpressed in a variety of human cancer types, including gastric cancer (46), breast cancer (47), glioblastoma (48), renal cell carcinoma (49) and osteosarcoma (50). In NSCLC, IGF-1R expression has been revealed to be upregulated, and significantly associated with tumor size, tumor grade and response to chemotherapy (25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1R is a transmembrane tyrosine kinase receptor of the insulin receptor family and contains two extracellular α subunits and two transmembrane β subunits (45). Numerous studies have reported that IGF-1R is frequently overexpressed in a variety of human cancer types, including gastric cancer (46), breast cancer (47), glioblastoma (48), renal cell carcinoma (49) and osteosarcoma (50). In NSCLC, IGF-1R expression has been revealed to be upregulated, and significantly associated with tumor size, tumor grade and response to chemotherapy (25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we found that ABCG2 expression level was signi cantly increased in patients with decreased disease free survival and poor response to chemotherapy. It was in accordance with previous study reporting that elevated levels of ABCG2 have a vital role in OS prognosis [19]. On the basis of these data, we proposed that ABCG2 may become a promising therapeutic target for OS patients.…”
Section: Discussionsupporting
confidence: 92%
“…A higher level of CD44 expression in OS tissues is apparent in patients with shorter survival and those with an unfavorable response to neoadjuvant chemotherapy [ 54 ]. Furthermore, CD44 expression is predictive of poor survival, metastasis, recurrence, and drug resistance in patients with OS [ 132 , 133 ].…”
Section: Ecm Components As Prognostic Biomarkers In Osmentioning
confidence: 99%